Knowledge, Attitudes, and Motivation Regarding Exclusive Breastfeeding Between Medical and Nonmedical Students: A Cross-Sectional Study - Lubis, Melviana; Rozi, Meisyah Putri (Makara Journal of Health Research, 2025)
Background: Exclusive breastfeeding provides substantial health benefits; however, disparities in knowledge and support persist. This study aimed to compare knowledge levels, attitudes, and motivation levels regarding exclusive breastfeeding between female medical and nonmedical students. Methods: A cross-sectional survey was conducted at Universitas Muhammadiyah Sumatera Utara and involved 314 students from the 2023 cohort. A validated questionnaire was used to assess knowledge levels (16 items), attitude (IIFAS, 16 items), and motivation (15 items). Data were analyzed using the chi-square test, odds ratio (OR), and Spearman’s correlation. Results: Medical students demonstrated significantly higher levels of knowledge (OR = 3.50; 95% CI: 1.93–6.33; p < 0.001), attitude (OR = 2.19; 95% CI: 1.34–3.58; p = 0.001), and motivation (OR = 2.81; 95% CI: 1.62–4.85; p < 0.001) toward exclusive breastfeeding than nonmedical students. However, misconceptions remain regarding the equivalence of formula to breast milk and the acceptability of breastfeeding in public. A moderate positive correlation was observed between knowledge and motivation levels (ρ = 0.375, p < 0.001). Conclusion: Although structured health education enhances students’ breastfeeding perspectives, it does not completely address sociocultural and practical barriers. Broader, interdisciplinary education and supportive environments may better prepare students as future mothers and breastfeeding advocates.